Effects of UV-B Radiation on the Performance, Antioxidant Response and Protective Compounds of Hazelnut Pollen - ÇETİNBAŞ GENÇ, ASLIHAN; SESAL, NÜZHET CENK (My University, 2022)
Increasing ultraviolet (UV) radiation is expected to become a problem in hazelnut cultivation. The aim of this study is to examine the effects of UV-B on hazelnut pollen. To this end, the pollens were exposed to UV-B for 1, 2, and 3 h at distances of 10, 20, 30, and 40 cm. Groups treated for 2 h at 20 cm and 3 h at 10 and 20 cm were identified as the most affected based on the results of viability, germination, and tube elongation. Further studies on these groups showed that UV-B does not change the DPPH radical scavenging activity for all groups. However, total phenolic compounds decreased after 3 h of treatment at 10 and 20 cm, while total flavonoid compounds decreased after all treatment groups. The UV-B absorbance of cytoplasmic and cell-wall-bound fractions decreased for all groups. The UV-B absorbance of the sporopollenin-derived fraction increased after 2 h of treatment at 20 cm but decreases after treatment for 3 h at 10 and 20 cm. In summary, exposure to UV-B for different times and distances adversely affected pollen grains in terms of pollen viability, germination rate, tube length, and the level of antioxidant molecules and UV-absorbing compounds.
Keywords: Tarımsal Bilimler; Ziraat; Bitki Koruma; Fitopatoloji; Agricultural Sciences; Agriculture; Plant Protection; Phytopathology; BİTKİ BİLİMLERİ; Bitki ve Hayvan Bilimleri; Tarım ve Çevre Bilimleri (AGE); PLANT SCIENCES; PLANT & ANIMAL SCIENCE; Agriculture & Environment Sciences (AGE); Küçük hayvanlar; Bitki Bilimi; Sağlık Bilimleri; Yaşam Bilimleri; Small Animals; Plant Science; Health Sciences; Life Sciences; antioxidant activity; hazelnut; pollen; UV-B-absorbing compounds; UV-B radiation; TUBE GROWTH; GERMINATION; SPOROPOLLENIN; VIABILITY; GRAINS; PLANTS; INVOLVEMENT; MORPHOLOGY; QUALITY; YIELD; antioxidant activity; hazelnut; pollen; UV-B-absorbing compounds; UV-B radiation